First discovery of the charophycean green alga Lychnothamnus barbatus (Charophyceae) extant in the New World. Issue 7 (27th July 2017) - Karol, Kenneth G.; Skawinski, Paul M.; McCourt, Richard M.; Nault, Michelle E.; Evans, Reesa; Barton, Martha E.; Berg, Matthew S.; Perleberg, Donna J.; Hall, John D.
Abstract : PREMISE OF THE STUDY: Although some species of Characeae, known as stoneworts, can be found on every continent except Antarctica, many species and some genera have limited geographic distributions. The genus Lychnothamnus, represented by a single extant species L. barbatus, was known only from scattered localities in Europe and Australasia until it was recently discovered in North America. METHODS: Morphological identifications were made from specimens collected in Minnesota and Wisconsin, USA. DNA sequences were obtained for three plastid‐encoded genes ( atpB, psbC, rbcL ) from seven putative Lychnothamnus samples from two states in the USA Distribution and abundance were estimated in each lake using point intercept surveys where surveyors sampled aquatic vegetation. KEY RESULTS: Fourteen lakes in Wisconsin and two lakes in Minnesota, USA, were found to harbor Lychnothamnus barbatus . These represent the first report of this rare charophycean extant in the New World. The North American specimens matched the morphological description for L. barbatus and were compared directly with the neotype. Phylogenetic results using three plastid‐encoded genes confirmed the identification placing New World samples with those from Europe and Australasia. Our phylogenetic analyses also confirmed the sister relationship between L. barbatus and Nitellopsis obtusa . CONCLUSIONS: Because this taxon is not known for aggressive invasiveness in its native range, it may have existed in heretofore‐undiscovered native populations, although the possibility that it is a recent introduction cannot be eliminated. The potential for discovery of novel lineages of green algae in even well‐studied regions is apparently far from exhausted.